2021
DOI: 10.1002/jee.20427
|View full text |Cite
|
Sign up to set email alerts
|

Inequity in graduate engineering identity: Disciplinary differences and opportunity structures

Abstract: Background: The retention of traditionally underserved students remains a pressing problem across graduate engineering programs. Disciplinary differences in graduate engineering identity provide a lens to investigate students' experiences and can pinpoint potential opportunity structures that support or hinder progress based on social and personal identities. Purpose: This study investigates the impact of discipline, gender, race/ ethnicity, advisor relationship, and years in a program on graduate engineering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(44 citation statements)
references
References 62 publications
4
40
0
Order By: Relevance
“…The result indicated statistically significant differences between minoritized students and nonminoritized students, and on average, the REI measured minoritized students as having fewer opportunities in their research experiences. These results and the prior research from Bahnson et al (2021) provide insight on why differences are sometimes measured between some groups and not in others: it depends on what construct is being measured.…”
Section: Resultssupporting
confidence: 62%
See 3 more Smart Citations
“…The result indicated statistically significant differences between minoritized students and nonminoritized students, and on average, the REI measured minoritized students as having fewer opportunities in their research experiences. These results and the prior research from Bahnson et al (2021) provide insight on why differences are sometimes measured between some groups and not in others: it depends on what construct is being measured.…”
Section: Resultssupporting
confidence: 62%
“…Borrego et al (2017) surveyed engineering master's and PhD students and found no significant gender differences in students' satisfaction in their research experiences between women and men. Bahnson et al (2021) studied opportunity structures in engineering PhD students' experiences and conducted a survey with 1754 participants and found no significant gender differences in students' identity as a researcher between women and men.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The experiences described by our participants point to ways policy and practice have failed to make engineering doctoral education equitable (Bahnson et al, 2021;Bancroft, 2018;Burt, Williams & Smith, 2018;Burt, Williams & Palmer, 2019;McGee, 2016;McGee & Martin, 2011;Perkins et al, 2020;Ramirez, 2014). The ruling relations of doctoral education function as intended to support to traditional students; while limiting success and generating differential educational experiences for TUSs (Pawley, 2019).…”
Section: Studies In Engineering Educationmentioning
confidence: 91%